PHILOSOPHICAL FOUNDATIONS OF THE THEORY OF POLITICAL COMMUNICATION - Ordenov, Serhii (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Politics, in its broadest sense, represents a set of social practices and discourses related to the exercise of power, through which forms and methods of governing society, social groups, and their relations are implemented. The aim and tasks are to carry out a philosophical reception of the theoretical foundations of political communication. Research methods include dialectical, historical, and comparative approaches combined with philosophical principles of objectivity and systemacity, as well as general scientific principles of correspondence and relativity. Research results. The philosophical conceptualization of political communication sets the focus of scholarly inquiry, shaping the optics of philosophical reflection and serving as a fundamental criterion that structures the construction of various theoretical frameworks, models, and approaches to explaining this phenomenon. Discussion. In the course of developing various philosophical schools, concepts, and views on communication, the philosophical understanding of the phenomenon of communication is generalized, taking into account the theoretical and methodological contributions of hermeneutics, phenomenology, analytic and pragmatic philosophy, among others. Conclusions. The conceptualization of political communication has taken place in close interaction between philosophical and empirical scientific knowledge, implying their mutual correlation, which can be described as interpenetration and reciprocal influence.